The Intervening Role of Self-Efficacy in the Impact of Family Environment and Entrepreneurship Education on Entrepreneurial Intentions - Hajar Dewantara; Muh. Jusri Jasman; Mutmainnah Mutmainnah; A. Ummi Amhar; Matthew Olufemi Adio (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This study aims to examine the effect of family environment and entrepreneurship learning on entrepreneurial interest with self-efficacy as an intervening variable. The method we use in this research is quantitative method. In this study also used a survey method with a questionnaire or koesener as a data collection instrument. The research population is all students in the faculty of economics and business majoring in entrepreneurship totaling 427 students. While the sampling technique uses proportional random sampling technique, which is calculated using Slovin with a sample size of 84 respondents or 22% of the total population. The research method used in this research is quantitative. This research can be a source of information or reference for teaching staff or lecturers in order to be able to direct and guide students related to the development of environmental influences and learning entrepreneurship to interest in entrepreneurship with self-efficacy as an intervening variable.